2021
DOI: 10.1089/cap.2020.0162
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy in the Management of Attention-Deficit/Hyperactivity Disorder in Children and Adolescents: A Review and Update

Abstract: Objective: Prescription of multiple medications concurrently for children and adolescents has increased in recent years. Examination of this practice has been undervalued relative to its incidence. This article reviews studies investigating effectiveness of medication combinations for youth with attention-deficit/hyperactivity disorder (ADHD). Methods: A literature search identified studies that combined two or more prescribed medications for the treatment of ADHD. Included studies focused on youth; had study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Multivariable analyses also revealed that both adolescent and adult patients in the ER only group experienced significantly fewer AEs than those in the ER + IR cohort. A recent study examining the effects of polypharmacy in children and adolescents treated for ADHD also concluded that monotherapy is preferable to reduce the number of AEs, when it yields an adequate response (Baker et al, 2021). It is important to consider that tolerability was identified by HCPs as a cardinal goal in treatment management in the current study, thus these two findings highlight another potential advantage of ER monotherapy over combination regimens: reduction in adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariable analyses also revealed that both adolescent and adult patients in the ER only group experienced significantly fewer AEs than those in the ER + IR cohort. A recent study examining the effects of polypharmacy in children and adolescents treated for ADHD also concluded that monotherapy is preferable to reduce the number of AEs, when it yields an adequate response (Baker et al, 2021). It is important to consider that tolerability was identified by HCPs as a cardinal goal in treatment management in the current study, thus these two findings highlight another potential advantage of ER monotherapy over combination regimens: reduction in adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Using more than one medication at any one time may be necessary, advantageous, and supported by various clinical guidelines, especially for hard to treat or comorbid cases. This is the case especially for ADHD, one of the most common reasons for attendance in CAMHS and a disorder with the largest amount of evidence for effective medication use (Baker et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, prospective longitudinal studies are consistent with that dismal prognosis; symptoms persist into adolescence and adulthood, stimulants have no demonstrable benefit beyond the controlled trial period (8), and stimulant use is positively associated with symptom persistence (9,10). While findings from carefully controlled prospective studies are useful, it is unclear how well they generalize to the context of community-based treatment, which is marked by high medication nonadherence, intermittent stimulant exposure (1113), and polypharmacy (14). While long needed, there have not been available community datasets that allow examination of real-world neural and symptom changes longitudinally in children being treated for ADHD with stimulants.…”
Section: Introductionmentioning
confidence: 99%
“…Carefully controlled prospective studies investigating stimulant exposure in ADHD have identified modulation in resting-state functional connectivity (rs-FC), measured by the temporal correlation of neural activity in a taskfree state, which is associated with chronic stimulant exposure and can partially explain symptom reduction among stimulant-treated children and adolescents (5)(6)(7). While controlled prospective studies are essential for teasing apart the relationships between stimulant exposure, functional characteristics of the brain, and heterogeneous symptom trajectories, the study protocols of controlled trials do not exactly match circumstances of real-world community treatment, which are marked by high nonadherence leading to intermittent stimulant exposure (8)(9)(10) and multiple psychotropic medication prescriptions (11). Medication adherence, described as taking medication in a way "corresponding to agreed recommendations from a clinician" (12), is particularly poor for adolescents with ADHD, with estimations ranging from 13.2% to 64% (8,13).…”
Section: Introductionmentioning
confidence: 99%